The quantity theory of money, 1870-2020 - Alexander Jung (European Central Bank (ECB), 2024)
This study re-assesses the validity of the quantity theory of money (QTM) for the very long sample, 1870 to 2020, for 18 industrial countries using the dataset from Jordà et al. (2017). It considers structural changes in the economic and financial sectors and changes in monetary policy frameworks. Three findings are presented. First, the results from panel cointegration tests show that the long-run relationship between excess money growth and inflation holds if longer runs of data are used. Second, panel regressions confirm the presence of long and variable lags in the monetary policy transmission, as predicted by Milton Friedman. For the full sample, the average speed of adjustment from excess money growth to inflation in industrial countries was about two years amid heterogeneity across time and countries. Third, the results show that over recent decades, structural change - coinciding with the Great Moderation and, in part, reflecting changes in payment technologies - has led to a collapse of QTM.
Keywords: B16; B23; E40; E50; N1; 330; Excess money growth; Great Moderation; payment technologies; structural change; panel cointegration tests